The prevalence of infection related death at Salt River Mortuary for the years 2013 and 2014 - Kruger, Maria Magdalena (Division of Forensic Medicine and Toxicology, 2017)
Infection related death is of major concern world-wide. This is especially true in developing countries where there is a high burden of disease. In some cases infections may present atypically and death occurs without a diagnosis in life. Many countries, including South Africa, classify these deaths as sudden unexpected or unexplained, which, under the Inquests Acts, necessitates a medico-legal autopsy. In order to understand the mechanisms underlying such deaths, a systematic review of the literature was undertaken on sudden death due to infection. Data from published research and reports identified many pathogens associated with sudden or unexplained death in infants and older individuals. However it remains important to understand locally relevant pathogens. In addition, many risk factors have been identified in different age groups but it is not known what risk factors are prevalent in a local setting and if these correspond to international trends. In order to contribute to local data a case file review was undertaken of infection related deaths at Salt River Mortuary between 1 January 2013 and 31 December 2014 (n=809). Deaths due to respiratory infections were the leading cause of death across all ages and in both sexes. It is not known to what degree this is a true reflection of the cause of death as the extent of autopsy, ancillary investigations and availability of ante-mortem clinical information varied widely. There has been a call for standardised protocols for the post-mortem investigation of these deaths and the data analysed reiterated this need. Many of the modifiable risk factors for infant death identified in the literature review were also identified in the Western Cape Metropole area, with the exception of sleeping position: side sleeping, as opposed to prone sleeping, was identified as the distinctive risk factor. In older individuals tuberculosis was identified as either the cause of death or a major contributor to comorbid conditions, which highlights the importance of further surveillance of vulnerable individuals. These data have provided insight into the extent of infection related death and associated risk factors in a local context. A standardised protocol for the investigation of these deaths across mortuaries would enable more accurate data to be collected which in turn could be fed back into the healthcare system.